2004
DOI: 10.1124/jpet.103.063073
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin A, but Not Tacrolimus, Inhibits the Biliary Excretion of Mycophenolic Acid Glucuronide Possibly Mediated by Multidrug Resistance-Associated Protein 2 in Rats

Abstract: The onset of diarrhea after the administration of mycophenolate mofetil (MMF) is possibly associated with the biliary excretion of its metabolite, mycophenolic acid glucuronide (MPAG). This study was undertaken to clarify the mechanism underlying the biliary excretion of MPAG. Intravenously administered mycophenolic acid (MPA, 5 mg/kg) rapidly disappeared from plasma and was efficiently excreted as MPAG in the bile of Wistar (26% of dose) and Sprague-Dawley rats (21% of dose) over 1 h. On the other hand, in sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
154
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(170 citation statements)
references
References 30 publications
(27 reference statements)
13
154
3
Order By: Relevance
“…(4) How can therapeutic concentrations be achieved in clinical practice? (5) What is the cost-effectiveness to maintain patients within the therapeutic window? In the past few years, large clinical trials and pharmacokinetic studies of renal recipients have provided new insights in this discussion.…”
Section: Renal Transplantationmentioning
confidence: 99%
See 2 more Smart Citations
“…(4) How can therapeutic concentrations be achieved in clinical practice? (5) What is the cost-effectiveness to maintain patients within the therapeutic window? In the past few years, large clinical trials and pharmacokinetic studies of renal recipients have provided new insights in this discussion.…”
Section: Renal Transplantationmentioning
confidence: 99%
“…This has been clearly shown for CsA with a 30 to 40% lower dose-normalized MPA exposure (and higher MPAG exposure) in patients who received CsA as compared with patients who received tacrolimus or sirolimus (18). The difference in MPA exposure, depending on the concomitant calcineurin inhibitor (CNI), is explained by a pharmacokinetic interaction of CsA with the main MPA metabolite 7-O-MPA glucuronide (7-O-MPAG) (5). CsA inhibits the multidrug resistance protein 2-mediated transport of 7-O-MPAG into the bile, leading to less enterohepatic circulation of MPA and hence lower exposure (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MPA is metabolized mostly via the uridine diphosphate glucuronyltransferase (UGT) system. The primary inactive metabolite is the phenolic glucuronide mycophenolic acid glucuronide (MPAG), which is transported from liver cells into bile most likely via the ATP-binding cassette transporter MDR1-related protein 2 (Mrp2) (11). Biliary MPAG then enters the gastrointestinal tract, where, under the catalytic action of glucuronidase that is shed from the intestinal flora, it is hydrolyzed back to MPA, which is then recycled into the bloodstream, the so-called enterohepatic circulation (EHC) pathway ( Figure 1).…”
Section: Mpa Pkmentioning
confidence: 99%
“…This reduces systemic MPA availability by decreasing the enterohepatic recirculation, leading to an elimination of the second MPA plasma concentration peak. [23][24][25][26][27][28][29] Limited data have been reported on MMF and tacrolimus drug interaction. In vitro data showed that tacrolimus may increase MPA plasma concentration due to inhibition of UGT.…”
Section: Interaction With Immunosuppressive Drugsmentioning
confidence: 99%